"A baby bump for women's rights": analysing Local and International Media Coverage of Prime Minister Jacinda Ardern's Pregnancy. Issue 8 (17th November 2022) - Galy-Badenas, Flora; Sommier, Mélodine
ABSTRACT: Very few studies have examined discourses about Heads of State who have been pregnant whilst in office. In January 2018, Jacinda Ardern, Prime Minister of Aotearoa New Zealand, announced her pregnancy and intention of taking six weeks of maternity leave, which sparked national and international interest. This study analyses the coverage of Ardern's pregnancy and contributes to literature on representations of female politicians. A thematic analysis of newspaper articles ( N = 158) from six countries (New Zealand, Australia, France, Ireland, the United Kingdom, & the United States) was conducted. Mild nuances between international and New Zealand data were observed. The analysis suggests that Ardern's pregnancy was presented as a cultural achievement, in part through the tension between local and universal dimensions, and as a symbolic event, notably through the interplay between normal and extraordinary aspects. The findings indicate that Ardern's pregnancy was represented as a step closer to gender equality by advancing women's cause in society and working places and renegotiating representations of fatherhood and masculinity. The notion of privilege was also important, in part because of its absence as a significant consideration in the data, which further revealed normative feminist discourses.